Association between prehospital physician involvement and survival after out-of-hospital cardiac arrest: A Danish nationwide observational study. (November 2016) - Hamilton, Annika; Steinmetz, Jacob; Wissenberg, Mads; Torp-Pedersen, Christian; Lippert, Freddy K.; Hove, Lars; Lohse, Nicolai
Abstract: Aim: Sudden out-of-hospital cardiac arrest (OHCA) is an important public health problem. While several interventions are known to improve survival, the impact of physician-delivered advanced cardiac life support for OHCA is unclear. We aimed to assess the association between prehospital physician involvement and 30-day survival. Methods: Observational study including persons registered with first-time OHCA of any cause in the Danish Cardiac Arrest Registry during 2005–2012. We used logistic regression analysis to assess the association between 30-day survival and involvement of a physician at any time before arrival at the hospital. Secondary outcomes were 1-year survival and return of spontaneous circulation (ROSC) before arrival at the hospital. The associations were explored in three multivariable models: a model with simple adjustment, a model with multiple imputation of missing variables, and a propensity score model where exposed subjects were matched 1:1 with unexposed subjects on a propensity score reflecting the probability of being assigned to the exposure group. Results: 21, 165 persons with OHCA during 2005–2012 were included. Overall, 10.8% of OHCA patients with physician involvement and 8.1% of OHCA patients without physician involvement before arrival at hospital were alive after 30 days, crude odds ratio (OR) = 1.37 (95% CI = 1.24–1.51), adjusted OR = 1.18 (95% CI = 1.04–1.34). Physician involvement was also positively associated with ROSC, OR = 1.09 (95% CI = 1.00–1.19); and with 1-year survival, OR = 1.13 (95% CI = 0.99–1.29). Conclusion: In this large population-based observational study, we found prehospital physician involvement after OHCA associated with better 30-day survival. This association was also found for ROSC, but with less certainty for 1-year survival.